Duality in Toni Morrison’s The Bluest Eye - Shwein, Hussein Nasir (International Journal of Psychosocial Rehabilitation, 2020)
To be a minority group in American society, black people should encounter different social and political conflicts, racism, oppression and segregation in their lives. They are affected by the beauty values of the dominated white culture, W.E.B DuBois (1903) emphasizes that the problem of twentieth century is the problem of color. Therefore, African- Americans don’t have a single identity, they suffer from the duality of identity or the concept of “double consciousness” which reduces them to be a subordinated group. The struggle of African American has been so long and hard and none can deny that the past of slavery has a great impact on them, and white discrimination and oppression have destroyed them. Therefore, this paper will focus on the female characters who quest for their identities and determines cases of the suppression of the black female as Pecola by patriarchal institutions. Toni Morrison argues that the black females have been afflicted by the concept of inter-racial racism that women have suffered from double oppression by white and black males due to the “double consciousness”.